Strategy Can No Longer Ignore Planetary Boundaries: A Call for Tackling Strategy's Ecological Fallacy - Bansal, Pratima (Tima); Durand, Rodolphe; Kreutzer, Markus; Kunisch, Sven; McGahan, Anita M. (Journal of Management Studies, 2025)
AbstractThe field of Strategy has its origins in Business Policy, which emphasized how firms could pursue important social aims that individuals and governments could not pursue otherwise. This emphasis shifted in the 1970s as the field turned towards economics for insights. Strategy scholars began to address how market‐ and industry‐level considerations, such as performance, price, and competition, were pursued by firms. By applying macro‐level principles and assumptions analogically to a more micro‐level of analysis, strategy scholars inadvertently committed what statisticians call an ecological fallacy. Educators and scholars in the field of Strategy started to accept the constructive consequences of growth, not only for the economy, but for every firm, without considering the implications for society and the natural environment. In so doing, Strategy scholarship inadvertently undermined its very ambition to advance social aims. Our Point advocates for reconsideration of the field's foundations so as to remediate the ecological fallacy and to address the climate and biodiversity crises. The goal is to offer a brighter and more relevant future for our discipline.